Seed Germination Enhancement of Two Balanites Species (B. aegyptiaca (L.) Del. and B. rotundifolia (Tiegh.) Blatt.) Using Different Presowing Treatments in Ethiopia - Mohammed Adefa Seid; Tigist Wondimu; Asfaw Degu; Awol Assefa (Scientifica)
B. aegyptiaca and B. rotundifolia are known to be multipurpose trees with various uses and values. Therefore, the aim of this study was to investigate the seed germination behaviours of B. aegyptiaca and B. rotundifolia under different presowing treatments. Hence, seeds were collected from the Central and Southern Ethiopian Rift Valley regions. Then, a total of 864 fruits (seeds) subjected to eight different presowing treatments and planted in pots arranged in a completely randomized design (CRD) were tested for each species. The mean germination percentage (GP), mean daily germination percentage (GD), mean germination time (GT), and mean germination index (GI) were computed. One-way ANOVA showed the presence of significant GP, GD, GT, and GI among treatment groups at p<0.05 under both Balanites species. For B. aegyptiaca, Tukey’s HSD test showed that seeds soaked with 98% H2SO4 for 10 minutes (98HSO10m) and 20 minutes (98HSO20m) have the highest GPs (87 ± 8.8 and 82 ± 10.2, respectively) that are significant at p<0.05. The seeds soaked in 75°C hot water for 10 minutes and subsequently cooled for 12 hours (HW75d), 98HSO10m, and 98HSO20m have the highest GDs (2%) that are significant at p<0.05. Moreover, 98HSO20m, 98HSO10m, and seeds soaked in cold water for 48 hours at room temperature of 25°C (CW48h) have the shortest GTs (24 ± 2.2, 25 ± 0.5, and 25 ± 1.3, respectively), and 98HSO10m and 98HSO20m have the highest GIs (1.04 ± 0.09 and 1.01 ± 0.08, respectively) that are significant at p<0.05. For B. rotundifolia, the control recorded the highest cumulative germination (i.e., 71), followed by CW48h (i.e., 51). However, Tukey’s HSD tests generally indicated that no treatment group resulted in significant differences in the means of GP, GD, GT, and GI at p<0.05. So, no treatment group was observed to enhance the germination of B. rotundifolia compared to the control. However, this study generally indicated potential seed enhancement technologies for B. aegyptiaca with greater implications for propagation, conservation, and sustainable utilization of the species in the agricultural and pastoral communities of Ethiopia.